Academic and Quality of Life Variables in Mexican University Students - García García, Jesús Alberto (2023)
Objective. To analyze the effect of expectations and goals of academic progress on the dimensions of the quality of life of Mexican university students. Method. The research was quantitative with a cross-sectional, open, observational design with descriptive and predictive scopes. The statistical techniques used were descriptive statistics, correlation coefficient and path analysis with the GLS method. Sampling was non-probabilistic for convenience, with a total of 465 participants. Results. For the resulting explanatory model the variable academic progress goals is a direct predictor of the physical function dimension. And academic expectations of outcome are a predictor of the emotional role and physical function dimensions.